Dual-Band Rectangular Microstrip Antenna of 5 and 6 Ghz for Iot Devices - Hsb, Umar Muaz`zad; Nugroho, Bambang Setia; Nur, Levy Olivia (eProceedings of Engineering, 2023)
Abstract—Modern IoT devices needs to transmit more data than its previous generations, this why the newer antenna has more frequency and also has more bandwidth than its previous generation as seen in the newest Wi-Fi 6E and Wi-Fi 6, Dual-Band and high frequency design can help to solve this crucial part of the IoT communication problems as an IoT Gateway antenna. Designed a Dual-Band Rectangular Microstrip antenna using a 5 and 6 GHz, using Epoxy FR4 for the substrate and copper for the patch and ground, both of this materials is the common materials for making an antenna and relatively cheap. The observation was done through the simulation step using 3D model simulation software and measurement of printed antenna. In the Simulation, the VSWR from both frequencies is reaching the target by VSWR below 2, the bandwidth for the 5 GHz is 140 MHz while its not reaching the maximum target of 160 MHz bandwidth for the Wi-Fi 6 standard, but its reached the minimum of 80 MHz bandwidth, for the 6 GHz bandwidth is 212 MHz, its reach the target bandwidth but it lacks additional channel for other 160 MHz, the value of gain reach the target by both frequency gain is more than 1.5 dBi.Keywords—Internet of Things (IoT), antenna, dual-band, microstrip antenna, rectangular patch